Creating the Arabian Gulf the British Raj and the invasions of the Gulf - Rich, P. J. (Middle East classics, 2009)
Even whether to call the Gulf "Arabian" or "Persian" is an unending argument. Regardless of its name, the Gulf is one of the most politically important regions of the world. Rich shows that the influences of Britain and India are far deeper than commonly acknowledged, and that the sheikhs are actually the creation of the British Raj. In its attempt to make sense of the complexity of Arab sheikhdoms in the Gulf, Creating the Arabian Gulf is an ideal book for students and scholars interested in Middle East studies and international relations.